PENGARUH ORIENTASI KEWIRAUSAHAAN DAN KARAKTER WIRAUSAHA TERHADAP KEBERHASILAN USAHA PADA UMK SENTRA KULINER DI SEMOLOWARU SURABAYA - Syahfarina, Savira; Nasution, Ute Ch.; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
Thel delvellolpmelnt of UMK in elach relgioln alsol has thel poltelntial tol assist natiolnal delvellolpmelnt and grolwth by delvellolping thel elcolnolmy and beling ablel tol crelatel adelquatel nelw jolbs. Thel elxistelncel olf UMK is ablel tol belcolmel a bridgel folr thel colmmunity so that thely dol nolt olnly relly oln elmplolymelnt, but arel ablel tol crelatel nelw jolbs. This study aims to deltelrminel thel elffelct olf elntrelprelnelurial olrielntatioln and elntrelprelnelurial charactelr oln businelss succelss at UMK Culinary Celntelrs in Selmollolwaru Surabaya. This study usels a quantitativel relselarch melthold approlach by colllelcting data using a quelstiolnnairel. Thel polpulatioln in this study welrel all 30 UMK olwnelrs of folold and belvelragel at thel Selmollolwaru culinary celntelr in Surabaya, with all melmbelrs olf thel polpulatioln beling thel relselarch samplel. Thel data analysis telchniquel usels multiplel linelar relgrelssioln analysis. Thel relsults sholweld that elntrelprelnelurial olrielntatioln had a significant elffelct oln businelss succelss at thel UMK Culinary Celntelr in Selmollolwaru, Surabaya. Elntrelprelnelurial charactelr has a significant elffelct oln businelss succelss at thel Culinary Selntra UMK in Selmollolwaru Surabaya. Elntrelprelnelurial olrielntatioln and elntrelprelnelurial charactelr havel a significant elffelct oln businelss succelss at thel UMK Culinary Celntelr in Selmollolwaru Surabaya. Keywords: Elntrelprelnelurial Olrielntatioln and Elntrelprelnelurial Charactelr and Businelss Succelss